Pengaruh Latihan Kicking Motion terhadap Jauhnya Tendangan Bola dalam Permainan Sepakbola Siswa Ku 15 Tahun di SSB Selabora Fik Uny Pada Tahun 2010 - Nurcahyo, Fathan (Universitas Negeri Semarang, 2012)
This study aimed to investigate the effect of exercise kicking motion to kick the ball away on a football game 15 years in the KU students SELABORA FIK UNY SSB in 2010. This research is a quasi-experimental (quasi experiment) using survey methods with data retrieval technique using tests and measurements. This study was a population (population sampling). Subjects in this study were all students SSB SELABORA FIK UNY 15 years old are 40 students who were divided into 4 groups. Collecting data using test and measurement using the test tool or instrument Ã¢â‚¬Å“Warner test of Soccer DrillsÃ¢â‚¬Â, from Barrow and Mc. Gee (1979) with units of meters (m). The results showed that: (1) There are differences in the effects of exercise kicking motion and a quick rhythm burden was lighter loads to kick away students SSB SELABORA FIK 15 years at Ã‚Â UNY Yogyakarta municipality in 2010. (2) There are differences in the influence of long legs and short legs to kick away FIK UNY students SSB SELABORA in 2010. (3) There is no interaction between exercise and long legs kicking motion to kick away students SSB SELABORA FIK 15 years at UNY Yogyakarta municipality in 2010.Ã‚Â